Incorporation of Partially Hydrolyzed Polyacrylamide With Zwitterionic Units and Poly(Ethylene Glycol) Units Toward Enhanced Tolerances to High Salinity and High Temperature - Lu, Gang; Zhao, Jikuan; Li, Shaoqi; Chen, Yuquan; Li, Chunfang; Wang, Youqi; Li, Dongxiang (Frontiers in Materials, 2021)
Partially hydrolyzed polyacrylamide (HPAM) was widely implemented to improve the rheological properties of displacing fluids, but the high temperature and salinity of the reservoir brine limited their applications. Herein, copolymers including HPAM, zwitterion-modified HPAM (z-HPAM), PEG-modified HPAM (p-HPAM) and zwitterion/PEG-modified HPAM (zp-HPAM) were prepared by free radical polymerization in an aqueous solution. The viscosity of these copolymers under different temperature and salinity were measured in aqueous solution. It is found that the viscosity of the HPAM under the harsh condition (90oC, 20x104 mg/L salinity) is only 9.6% of that value under the normal condition (25oC, pure water), while the z-HPAM can significantly improve salt resistance by the effects of salting-in effect and intermolecular electrostatic crosslinking, showing a viscosity retention of 22.9% under the harsh condition. The addition of PEG-containing monomer can strengthen hydrogen bonding between the polymer chains and form a sterically ordered structure with improved salinity and temperature resistance. The synergistic effect of zwitterion units and PEG units endows the zp-HPAM with good salinity and temperature resistance, thus the sample viscosity under the harsh condition remains 170 mPa•s, which retains 29% of the value under the normal condition. The enhanced rheology properties of the zp-HPAM under the harsh condition are significant for the enhanced oil recovery of water-soluble polymer flooding.